Ultrasonic bioacoustics and stridulum morphology reveal cryptic species among Lipotactes big-eyed katydids (Orthoptera: Tettigoniidae: Lipotactinae) from Borneo. Issue 5 (3rd July 2020) - Tan, Ming Kai; Ingrisch, Sigfrid; Wahab, Rodzay BIN Haji Abdul; Japir, Razy; Chung, Arthur Y. C.
Abstract : Lipotactinae is an elusive monophyletic subfamily of katydids (Orthoptera: Tettigoniidae) unique to Asia and comprising two genera – Lipotactes and Mortoniellus . Nearly nothing is known beyond their original descriptions. The stridulum morphology is rarely examined and described in taxonomy and their acoustics are only known for six species, none of which is from Borneo. New Lipotactes specimens collected from Borneo – Belait and Kuala Belalong in Brunei and Sandakan in Sabah – were initially identified as Lipotactes alienus and/or Lipotactes virescens based on traditional morphological characters. However, the structures of male calling songs of individuals from Kuala Belalong and Sandakan were profoundly different from each other and from the known songs of L. virescens from Thailand and Peninsular Malaysia. This led us to examine the morphology of the Bornean specimens more closely. By integrating call structures, stridulum morphology, and traditional morphology, we establish that the specimens from Borneo are different from L. virescens and that the populations from Kuala Belalong, Belait, and Sandakan represent different ethospecies. Here, we describe the species from Sandakan as Lipotactes kabili sp. nov. We also demonstrate that both stridulum morphology and call structures can be useful in separating Lipotactinae species because inter-specific differences are larger than intra-specific differences. http://zoobank.org/urn:lsid:zoobank.org:pub:A81579A3-CD0A-453C-BE03-236A21544031 http://zoobank.org/urn:lsid:zoobank.org:act:B89DB3B2-4913-4A6D-9D8D-91AFC5EEDDF8